Listening Skills of College Freshmen of the Nueva Ecija University of Science and Technology - Tamayo, Vladimir Tolentino (International Journal of English Literature and Social Sciences (IJELS), 2019)
Abstract: The study evaluated the listening skills of college freshmen of the Nueva Ecija University of Science and Technology based on the five stages of listening with the use of descriptive-correlational research. The researcher found out that most respondents, regardless of their profile, use their listening skill in listening to Tagalog music during the day through a medium (mostly mobile phones) accessible to them at all times. However, most respondents have only an average listening skill proved that they have a limited listening capability that needs to be addressed appropriately. Similarly, the respondents' academic performance could be affected if their listening skills would not be improved. Hence, intervention programs or activities that could enhance the listening competence of NEUST freshmen in learning the English language is needed and shall be regularly practiced.